Tricks of the trade in glycoscience: the preparation and analysis of a blood group A-active mucin glycoprotein. - Mulloy,B; Feizi,T (Biochem J, 2014)
Many aspects of glycosylation are conserved among animals, and it can be advantageous and sometimes critical to identify a readily available and abundant source of carbohydrate material that harbours a hard-to-characterize antigen or ligand of interest. The Biochemical Journal Classic paper by Morgan and King is a well-written account of serviceable methods for the extraction and quantification of a carbohydrate antigen. These methods were highly influential in subsequent studies of the blood group antigens. Some of these tricks of the trade still have a place in modern glycobiology.